Circulating Cell-Free DNA-Based Detection of Tumor Suppressor Gene Copy Number Loss and Its Clinical Implication in Metastatic Prostate Cancer - Dong, Xiaoxi; Zheng, Tiantian; Zhang, Minhua; Dai, Chao; Wang, Lili; Wang, Lei; Zhang, Ruipeng; Long, Yuan; Wen, Danyi; Xie, Feng; Zhang, Yue; Huang, Yong; et al. (Frontiers in Oncology, 2021)
Current liquid biopsy assays lack sufficient sensitivity to detect copy number loss, which limits the interrogation of critical tumor suppressor gene deletions during cancer progression and treatment. Here we describe a liquid biopsy assay with improved sensitivity for detection of copy number loss in blood samples with low levels of circulating tumor DNA, and demonstrate its utility by profiling PTEN, RB1 and TP53 genetic loss in metastatic prostate cancer patients.